Drying Methods Alter Angiotensin-I Converting Enzyme Inhibitory Activity, Antioxidant Properties, and Phenolic Constituents of African Mistletoe ( L) Leaves - Ganiyu Oboh PhD; Olasunkanmi Seun Omojokun MTech; Adedayo Oluwaseun Ademiluyi PhD (SAGE Publishing, 2016)
This study investigated the most appropriate drying method (sun drying, oven drying, or air drying) for mistletoe leaves obtained from almond tree. The phenolic constituents were characterized using high-performance liquid chromatography-diode array detector, while the inhibitory effect of the aqueous extracts of the leaves on angiotensin-I converting enzyme (ACE) was determined in vitro as also the antioxidant properties. Oven-dried extract (kidney [276.09 μg/mL] and lungs [303.41 μg/mL]) had the highest inhibitory effect on ACE, while air-dried mistletoe extract (kidney [304.47 μg/mL] and lungs [438.72 μg/mL]) had the least. Furthermore, the extracts dose-dependently inhibited Fe 2+ and sodium nitroprusside-induced lipid peroxidation in rat's heart and kidney. Also, all extracts exhibited antioxidative properties as typified by their radical scavenging and Fe-chelating ability. Findings from this study revealed that oven drying is the best of the 3 drying methods used for mistletoe obtained from almond host tree, thus confirming that diversity in drying methods leads to variation in phenolic constituents and biological activity of plants.